2011
DOI: 10.1002/ijc.26312
|View full text |Cite
|
Sign up to set email alerts
|

The cancer stem cell niche—there goes the neighborhood?

Abstract: The niche is the environment in which stem cells reside and is responsible for the maintenance of unique stem cell properties such as self-renewal and an undifferentiated state. The heterogeneous populations which constitute a niche include both stem cells and surrounding differentiated cells. This network of heterogeneity is responsible for the control of the necessary pathways that function in determining stem cell fate. The concept that cancer stem cells, a subpopulation of cells responsible for tumor initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
173
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(183 citation statements)
references
References 130 publications
3
173
0
2
Order By: Relevance
“…Similar to normal stem cells, CSCs are defined by multiple functional properties: 1) CSCs can go through unlimited cell divisions; 2); CSCs are on the top of tumor hierarchy and can generate all cell types in a tumor; 3) some CSCs are able to shuttle between quiescent, slowcycling and active states; 4) some CSCs can exhibit resistance to conventional cancer therapies (Baccelli and Trumpp, 2012). Recent studies have indicated that these functional properties of CSCs might be sustained by tumor microenvironment, termed as "niche" (Cabarcas et al, 2011). The niche is the environment in which CSCs reside, and it is responsible for maintaining the self-renewal capacity and undifferentiated state of CSCs (Oskarsson, 2013).…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…Similar to normal stem cells, CSCs are defined by multiple functional properties: 1) CSCs can go through unlimited cell divisions; 2); CSCs are on the top of tumor hierarchy and can generate all cell types in a tumor; 3) some CSCs are able to shuttle between quiescent, slowcycling and active states; 4) some CSCs can exhibit resistance to conventional cancer therapies (Baccelli and Trumpp, 2012). Recent studies have indicated that these functional properties of CSCs might be sustained by tumor microenvironment, termed as "niche" (Cabarcas et al, 2011). The niche is the environment in which CSCs reside, and it is responsible for maintaining the self-renewal capacity and undifferentiated state of CSCs (Oskarsson, 2013).…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…It seems generally agreed upon that somatic mutations and other forms of evolutionary pressure, such as the niche effect, 20 can lead to tumour heterogeneity that even extends to the highest hierarchical order, that of tumour stem cell. 21 Our therapeutic decisions are invariably based on the (molecular) histological features of the dominant, i.e.…”
Section: New Therapeutic End Pointsmentioning
confidence: 99%
“…There are 2 types of CSC niches, osteoblast CSC niche and vascular CSC niche, that regulate CSC self-renewal and differentiation [3,10]. The niches consist of CSCs, stromal cells, and blood vessels.…”
Section: Tumor Neovascularization and Cancer Stem Cell Nichementioning
confidence: 99%
“…In addition, aggressive tumor cells (such as cancer stem cells) are important in the initiation and development of a malignant TME by active participation in tumor neovascularization and generation of a cancer stem cell niche [9][10][11]. Although stromal cells are considered a promoter during the genesis of the TME [12], dysfunction of stromal cells may induce generation of cancer stem cells and malignant tumors [13].…”
Section: Introductionmentioning
confidence: 99%